2006
DOI: 10.1152/ajpheart.01373.2005
|View full text |Cite
|
Sign up to set email alerts
|

Differential modulation of Kv4.2 and Kv4.3 channels by calmodulin-dependent protein kinase II in rat cardiac myocytes

Abstract: In this work we have combined biochemical and electrophysiological approaches to explore the modulation of rat ventricular transient outward K(+) current (I(to)) by calmodulin kinase II (CaMKII). Intracellular application of CaMKII inhibitors KN93, calmidazolium, and autocamtide-2-related inhibitory peptide II (ARIP-II) accelerated the inactivation of I(to), even at low [Ca(2+)]. In the same conditions, CaMKII coimmunoprecipitated with Kv4.3 channels, suggesting that phosphorylation of Kv4.3 channels modulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
69
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(81 citation statements)
references
References 43 publications
(61 reference statements)
12
69
0
Order By: Relevance
“…Notably, in cardiomyocytes KChIP2 may form a complex with Cav1.2 [68,69], maybe in combination with Kv4 channels. Also, CaMKII, which seems to play a critical role in the Ca 2+ -dependent regulation of Kv4/KChIP channels [22], may participate in this cardiac signaling complex [9496]. Finally, it has to be examined whether other sources of Ca 2+ , including transmitter-gated channels like N-methyl-D-aspartic acid (NMDA) receptors, or ER Ca 2+ channels like the ryanodine and the IP3 receptor, are able to acutely modulate the gating of Kv4/KChIP channel complexes.…”
Section: Acute Modulation Of the Kv4/kchip Channel Complex By Cytoplamentioning
confidence: 99%
“…Notably, in cardiomyocytes KChIP2 may form a complex with Cav1.2 [68,69], maybe in combination with Kv4 channels. Also, CaMKII, which seems to play a critical role in the Ca 2+ -dependent regulation of Kv4/KChIP channels [22], may participate in this cardiac signaling complex [9496]. Finally, it has to be examined whether other sources of Ca 2+ , including transmitter-gated channels like N-methyl-D-aspartic acid (NMDA) receptors, or ER Ca 2+ channels like the ryanodine and the IP3 receptor, are able to acutely modulate the gating of Kv4/KChIP channel complexes.…”
Section: Acute Modulation Of the Kv4/kchip Channel Complex By Cytoplamentioning
confidence: 99%
“…KN-93 competitively inhibits Ca 2ϩ -CaM binding to Ca 2ϩ /CaMKII (5, 7, 31a). Although prior studies examined the effects of W-7 and KN-93 on the native Ca 2ϩ and K ϩ currents in cardiac myocytes, the effects of these two agents on the gating and permeation properties of K v 4 channels have not been analyzed in detail (5,19,38,42,60,69).…”
Section: Calmodulin (Cam) Is a Ubiquitous Camentioning
confidence: 99%
“…In addition, the effects of KN-93 on the A-type current in the central nervous system and smooth muscle of the gastrointestinal tract have been studied (1,2,11,35,39,40). Ca 2ϩ /CaMKII activation and inhibition have been shown to modulate A-type current in colonic and gastric myocytes and in cardiac myocytes (1,2,19,39,40). Sergeant et al (63) demonstrated that KN-93 and a constitutively active Ca 2ϩ / CaMKII modulated inactivation, recovery from inactivation, and the steady-state inactivation relation of the heterologously expressed K v 4.3 channel.…”
Section: Calmodulin (Cam) Is a Ubiquitous Camentioning
confidence: 99%
See 2 more Smart Citations